Assessment of Air Pollution Impacts on Population Health in Bejaia City, Northern Algeria. - Fatima Benaissa; Rezak Alkama; Isabella Annesi-Maesano (Tehran University of Medical Sciences, 2014)
To assess the health impact of air pollution on Bejaia population in the north of Algeria, we carried out a descriptive epidemiologic inquiry near the medical establishments of three areas.From hospital admissions registers, we collected data on the hospital mortality and admissions relating to the various cardiorespiratory pathologies generated by this type of pollution. In parallel, data on the automobile fleet of Bejaia and other measurements were exploited to show that the pollutants concentrations are strongly correlated with the urban traffic concentration.This study revealed that the whole of the population is touched, but the sensitivity to pollution can show variations according to the age, the sex and the residence place. Population of Bejaia town marked the most raised death and morbidity rates, followed by that of Kherrata. Weak rates are recorded for the rural population of Feraoun. Stronger correlation (>0.9) is evident amongst CO and deaths due to asthma and COPD in Béjaia city.This approach enables us to conclude that the population of Béjaia could not escape the urban pollution generated by her old automobile fleet. Installation of a monitoring and measuring site of air pollution in this city could provide a beneficial tool to protect its inhabitants by informing on air quality they breathe and the measures to following order to minimize the impacts on their health and by alerting the authorities during the critical situations.